What was Ellis Island? - Demuth, Patricia; Groff, David 1956- (New York, New York Grosset & Dunlap an imprint of Penguin Group (USA) LLC, 2014)
Describes the history of Ellis Island, a gateway for many immigrants coming to the United States in the nineteenth and early twentieth centuries, and details the restoration of the landmark and its reopening as a museum
The world around us
Includes bibliographical references (page 106)
1
Keywords: Ellis Island Immigration Station (N.Y. and N.J.); Ellis Island Immigration Station (N.Y. and N.J.) -- History -- Juvenile literature; Ellis Island Immigration Station (N.Y. and N.J.) -- History; Emigration and immigration; United States -- Emigration and immigration -- History -- Juvenile literature; United States; United States -- Emigration and immigration -- History; History; Juvenile works